(3GdCbQGHGPjf Ydi JQjJH GdYdds - (3eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO, GdfLjH GdSeQbfOj , J (B619 (3g` s ((3Rjf GdYGHOjf Hf eMeO HGHG s)
(3ChdgG (B:s
(3COhjI Ydd GdQCS (B: (3MH GdbhbGjG , GdCOhGA GdQCS GdGeJdGFjI ef GdQWhHI CjGQfL ajbQG , YTQI OQGge , TMe GdMfXd KdGKI OQGge hKdK s
(3BNQgG (B:s
(3hbO jSbi OGfbkG ef GdPGQGQjL eY OGfb ef GdYOS GdebTQ HeGA aGJQ HYO Cf jfbY GdPGQGQjM ai GdQGFH jhekG hdjdI , hjHOd GdQGFH hjaYd KdGK eQGJ , ajchf cGajkG Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdfSNI HgG MhGTs
(3fSNI KGfjI ef GdbSe GdSGOS ef GdfLjHjGJs
(3YdjgG ebGHdI SfI (B907(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs